E-cigarettes may serve as a gateway to conventional cigarettes and other addictive drugs - Grace Chen; Shafiqur Rahman; Kabirullah Lutfy (Advances in Drug and Alcohol Research, 2023)
Electronic cigarettes (e-cigarettes) are devices that allow the user to inhale nicotine in a vapor, and are primarily marketed as a means of quitting smoking and a less harmful replacement for traditional cigarette smoking. However, further research is needed to determine if vaping nicotine via e-cigarettes can be effective. Conversely, nicotine has been considered a gateway drug to alcohol and other addictive drugs and e-cigarettes containing nicotine may have the same effects. Previous reports have shown that e-cigarette use may open the gate for the use of other drugs including conventional cigarettes, cannabis, opioids, etc. The increasing prevalence of e-cigarettes, particularly among youth and adolescents in the last decade have led to an increase in the dual use of e-cigarettes with alcohol, cannabis, and other illicit drug use like heroin and 3-4-methylenedioxymethamphetamine (MDMA). The advent of e-cigarettes as a device to self-administer addictive agents such as cocaine and synthetic cathinones may bring about additional adverse health effects associated with their concurrent use. This review aims to briefly describe e-cigarettes and their different generations, and their co-use with other addictive drugs as well as the use of the device as a tool to self-administer addictive drugs, such as cocaine, etc.